DA’WAH STRATEGY OF SULAIMANIYAH PESANTREN IN INSTILLING AKHLAQUL KARIMAH MAHASANTRI: (Study on Sulaimaniyah Islamic Boarding School for Sultan Students) Selahaddin Banda Aceh) - Ridwan Muhammad Hasan, Ridwan Muhammad Hasan; Maulana Arifan (Jurnal Ikhtibar Nusantara, 2025)
The progress of the times has caused many young people to stray from Islamic values, especially akhlaqul karimah. Institutions such as Islamic boarding schools are needed as a solution to minimise and even change this gap, transforming it in accordance with Islamic values themselves. A wise strategic process is required to successfully produce young people who are Islamic and possess akhlaqul karimah. This study is titled "Strategies of Sulaimaniyah Islamic Boarding School in Instilling Moral Values Among Its Students (A Study at Sulaimaniyah Islamic Boarding School for Sultan Selahaddin Students)." The objective of this study is to identify the strategies employed by the Sulaimaniyah Islamic Boarding School in Sultan Selahaddin to instill akhlaqul karimah in its students, as well as the supporting and hindering factors in the process of instilling these values. The research method used is qualitative, with data collection techniques including observation, interviews, and documentation. The research subjects consist of 7 individuals, comprising 1 boarding school leader, 2 teachers, and 4 students. The da’wah strategies implemented include enforcing regulations that foster good habits, such as prioritising manners over knowledge, teachers setting a good example, the absence of violence, and sincerity. The supporting factors in the process of instilling akhlaqul karimah values include a positive external environment, students having a vision and mission, and synchronisation between teachers, students, and donors. The inhibiting factors include a negative social environment, students having other goals while living in the dormitory, lack of synchronisation between teachers and students, and cultural differences between students and teachers.